Experimental investigation of additively manufactured MS-300 maraging steel samples: Microstructure and mechanical properties - Kumar M.; Kumar S.; Singh P.K.; Kumar Srivastava B. (My University, 2025)
This study investigates the fabrication and characterization of maraging steel-300 samples produced by the laser-powder bed fusion (L-PBF) process, using X3NiCoMoTi-18-9-5 metal powder. Both conventional manufacturing (CM) and L-PBF samples undergo solution and age-hardening heat treatments. The age-hardening process resulted in the formation of fine intermetallic phases, including FeMo and Fe-Delta precipitates. Comparative analysis revealed that age-hardened samples produced by L-PBF and CM exhibit higher microhardness with comparable densities. Micro-hardness of as-built and age-hardened L-PBF maraging steel-300 samples increased by 41% and 8% with respect to that of as-received and age-hardened conventional maraging steel-300 samples. In addition to this, the yield strength of as-built and age-hardened L-PBF maraging steel-300 samples increased by 3% and 1.5% with respect to that of as-received and age-hardened conventional maraging steel-300 samples. After solution treatment, optical micrographs of L-PBF samples exhibited a finer grain structure compared to CM samples. © IMechE 2024.